Campus Commons: Analysis of IIT Patna’s Public open Spaces - Nazish Abid; Mazharul Haque (Qubahan Academic Journal)
The Public open spaces offer amenities including areas for social interaction and physical activity, which are crucial for the overall wellness of society and the enhancement of living quality. Many studies on POSs have been conducted in developed countries (the US, Australia, and Europe, particularly Germany, Spain, and France). POSs for the Indian context haven't been thoroughly studied, though. Using importance-performance analysis (IPA), this study attempts to investigate the role and effectiveness of public open spaces on the campus of National Institute of Technology, Patna, India. It has been noted that stakeholders' perceptions of the importance & satisfaction, from the use of public open spaces within the IIT Patna campus, varies. Consequently, this study could be useful in determining the importance and satisfaction of public open spaces, enabling the prioritization of these areas in order to enhance management and restore them in order to accomplish environmental sustainability locally. Furthermore, this study recommends that public open spaces' benefits to education, recreation, & the environment be taken into account by those in authority over campus planning early on.